PELAKSANAAN PROTOKOL CHSE (CLEAN, HEALTH, SAFETY, ENVIRONMENT SUSTAINABILITY) PADA MASA ENDEMI COVID-19 DI OBJEK WISATA PANTAI AIR MANIS KOTA PADANG - Yohana Devirda Novich; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The CHSE protocol is the implementation of a health protocol that relies on Clean, Health, Safety as a guideline for tourism industry and creative economy businesses. Kemenparekraf as an organization that regulates tourism and the creative economy strengthens the implementation of the CHSE protocol so that it can be implemented very well by business elements in the local area. Air Manis Beach is a marine tourism object located in South Padang District, Padang City, West Sumatra. Air Manis Beach is closely related to the legend of Batu Malin Kundang in West Sumatra. In West Sumatra Air Manis Beach is one of the tourist attractions that is undergoing the CHSE certification process. This study uses a qualitative method with a descriptive approach to describe the actual situation by collecting data using data collection techniques from observation, documentation and interviews. The results of this study can be seen how the implementation of the CHSE protocol has been implemented at the tourist object, has it been implemented by managers or visitors and what forms of the CHSE protocol have been implemented at the Air Manis Beach tourist attraction. Keywords : Implementation, CHSE Protocol, Covid-19, Air Manis Beach